2017
DOI: 10.1002/chem.201605148
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Insight Into Reactivity Differences Between Malonic Acid Half Thioesters (MAHT) and Malonic Acid Half Oxyesters (MAHO)

Abstract: An efficient two-step synthesis of structurally and functionally diverse thiophenol- and (cyclo)alkyl-derived malonic acid half thioesters (MAHTs) and phenol-derived malonic acid half oxyesters (MAHOs) has been achieved using cheap, readily available and easily handled starting materials. The synthesis of the MAHTs and MAHOs (the majority of which have not been previously reported) is readily scalable to afford gram quantities of product. In a hydrogen→deuterium exchange, an interesting stereoelectronic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Malonic acid monothioesters are known to be more reactive C-nucleophiles than the corresponding esters [ 41 ]. Therefore, we studied the decarboxylative addition of compound 1b as representative example to substrates 2a – m ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Malonic acid monothioesters are known to be more reactive C-nucleophiles than the corresponding esters [ 41 ]. Therefore, we studied the decarboxylative addition of compound 1b as representative example to substrates 2a – m ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of an amine base, MAHT 3 fails to react with enolate acceptors such as 4 to yield the addition product A (or 5 ) and prefers to decarboxylate into the irrelevant product D (or 6 ) instead (Figure ). Often based on tertiary amines, particularly those in cinchona alkaloids, several catalysts have been reported to achieve enolate addition, and related reactions have already been realized on solid surfaces (without electric fields) . We have previously shown that the intrinsic selectivity in favor of decarboxylation rather than enolate addition can be reversed using anion−π catalysts. , Namely, these catalysts are expected to recognize planar enolate tautomers with delocalized negative charge, which undergo addition before decarboxylation ( RI-A , TS-A ) rather than decarboxylative deplanarized tautomers with localized charge ( TS-D ).…”
mentioning
confidence: 99%
“…The harsh reaction conditions (the presence of a strong acid and high temperature up to 130 °C) pushed us to switch attention to the organocatalytic decarboxylative cascade strategy for the synthesis of 3,4-unsubstituted coumarins. The reaction between salicylaldehyde and malonic acid half-thioester 19 catalysed by a combined benzylamine (20 mol%) and Et 3 N (20 mol%) system turned out to be useful for the preparation of 2a , 2b , and 2d in low to good yields (Scheme 1, Method B). 17 The reduction of the NO 2 group in intermediates 3a , 3b , and 3d was very efficient under an Fe–AcOH system in EtOH, resulting in the formation of the desired products 4a , 4b , and 4d in good to high yields (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%